Making Difficult Decisions in Major Military Trauma: A Crew Resource Management Perspective. Issue Volume 157:Issue (2011)Supplement 3 (1st September 2011) - Midwinter, MJ; Mercer, S; Lambert, AW; Rond, MJ de
Abstract : The purpose of this article is to consider three underappreciated but important features of high performance teams: the trade-off relation between social and technical competence, the relevance of team size on productivity, and the inevitability of tensions that, while often experienced as dysfunctional, are in fact quite useful. It does so by reviewing a series of related studies in aviation and the organisation sciences, and by extrapolating insights for crew resource management in major military trauma along two generic themes: team context and team process.